The Role of Semantics in Humor: A Study of Wordplay and Double Meanings - Heltri Firdayati Samongilailai; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This article aims to analyze the role of semantics in constructing humor, specifically through mechanisms of wordplay and double meanings. Using a literature review method, this study synthesizes findings from recent linguistic and pragmatic research related to humor strategies. The analysis shows that lexical ambiguity, especially involving homonyms and polysemy, serves as the primary foundation for verbal humor. Patterns of phonological wordplay, morphological manipulation, and shifts in meaning are identified as key strategies that enable multiple interpretations and the emergence of humorous effects. The study also emphasizes the important role of context and pragmatic knowledge in interpreting ambiguity and resolving semantic contradictions. These findings imply that humor is not only a linguistic phenomenon but also a cognitive process that requires the active involvement of listeners in understanding semantic structures and contextual information.